2020
DOI: 10.1159/000511915
|View full text |Cite
|
Sign up to set email alerts
|

IFIT Proteins Are Involved in CXCL10 Expression in Human Glomerular Endothelial Cells Treated with a Toll-Like Receptor 3 Agonist

Abstract: Introduction: Various viruses including a novel coronavirus (SARS-CoV-2) can infect the kidney. When viruses invade the glomeruli from the bloodstream, glomerular endothelial cells (GECs) initiate the innate immune reactions. We investigated the expression of interferon (IFN)-induced protein with tetratricopeptide repeats (IFIT) 1/2/3, antiviral molecules, in human GECs treated with a toll-like receptor (TLR) 3 agonist. Role of IFIT1/2/3 in the expression of C-X-C motif chemokine ligand 10 (CXCL10) was also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…IFIT3 positively regulates IFN‐β and the OAS RNase L pathway to degrade RNA to inhibit KSHV lytic replication, in addition to potentially directly targeting viral mRNA 10,11 . IFIT3 may increase the expression of CXCL10 that induces lymphocyte chemotaxis and inhibits the replication of virus 49 . IFIT3 induces IFN signaling pathway and represses adenoviral immediate early gene expression 42 .…”
Section: Role Of Ifit3 In Antiviral Innate Immunitymentioning
confidence: 99%
“…IFIT3 positively regulates IFN‐β and the OAS RNase L pathway to degrade RNA to inhibit KSHV lytic replication, in addition to potentially directly targeting viral mRNA 10,11 . IFIT3 may increase the expression of CXCL10 that induces lymphocyte chemotaxis and inhibits the replication of virus 49 . IFIT3 induces IFN signaling pathway and represses adenoviral immediate early gene expression 42 .…”
Section: Role Of Ifit3 In Antiviral Innate Immunitymentioning
confidence: 99%
“…IFIT genes, particularly IFIT1, work in concert with other ISGs to inhibit viral translation by binding viral mRNAs that mimic host mRNAs due to the presence of 5′ cap-1 structures ( 33 , 34 ), which SARS-CoV-2 contains ( 35 ). The IFIT proteins also increase the expression of CXCL10 ( 36 ), the 2nd most upregulated gene in our analysis, which induces lymphocyte chemotaxis and may inhibit the replication of infected viruses. Only one study has identified IFIT1 in vitro during COVID-19 infection ( 37 ).…”
Section: Discussionmentioning
confidence: 63%
“…IFIT genes, particularly IFIT1, work in concert with other ISGs to inhibit viral translation by binding viral mRNAs that mimic host mRNAs due to presence of 5’ cap-1 structures [33, 34], which SARS-CoV-2 contains [35]. IFIT proteins also increase the expression of CXCL10,[36] the 2 nd most upregulated gene in our analysis, which induces lymphocyte chemotaxis and may inhibit the replication of infected viruses. Only one study has identified IFIT1 during COVID-19 in vitro [37].…”
Section: Discussionmentioning
confidence: 98%